INTERRELATION BETWEEN THE FORMATION AND IMPLEMENTATION OF INNOVATION AND INVESTMENT DEVELOPMENT STRATEGIES OF BANKING INSTITUTIONS AND ENTERPRISES UNDER CONDITIONS OF WAR CHALLENGES (INNOVATIVE ECONOMY, 2026)
Chaikovskyi Ya.I., Olikhovska M.V., Chaikovskyi Ye.Ya. INTERRELATION BETWEEN THE FORMATION AND IMPLEMENTATION OF INNOVATION AND INVESTMENT DEVELOPMENT STRATEGIES OF BANKING INSTITUTIONS AND ENTERPRISES UNDER CONDITIONS OF WAR CHALLENGESPurpose. The aim of the article is to study the interrelation between the formation and implementation of innovation and investment development strategies of banking institutions and enterprises, as well as to substantiate the mechanisms of their mutual coordination in the context of financial system transformation and the intensification of innovative processes in the economy.Methodology of research. The study applies methods of analysis and synthesis, a systems approach to examine the theoretical foundations of innovation and investment development of banks and enterprises and to identify interrelations between elements of strategic management, as well as comparative analysis to compare the features of innovation and investment strategies in the banking and corporate sectors. A forecasting method is used to substantiate the prospects for developing cooperation between banks and enterprises under conditions of digital transformation.Findings. The theoretical foundations of forming innovation and investment strategies of banks and enterprises have been revealed, and their essence and characteristics in the financial and corporate sectors have been defined. The interrelation between innovation and investment activities has been substantiated as a basis for the strategic development of economic entities. Directions for improving the effectiveness of interaction between the banking and real sectors of the economy have been proposed through the implementation of digital technologies, innovative financial instruments, public and private partnership mechanisms.Originality. Further development has been given to theoretical provisions on mechanisms for coordinating innovation and investment development strategies of banks and enterprises under conditions of digital transformation of the economy, and theoretical and methodological approaches to studying the interrelation between their formation and implementation have been improved.Practical value. The obtained results can be used by banking institutions and enterprises in the formation and implementation of innovation and investment development strategies, as well as in improving mechanisms of interaction between the financial and real sectors of the economy.Key words: innovation and investment development, banking institutions, enterprises, digitalization, financial innovations, banking sector, real sector of the economy, innovation activity, investment strategies, investment resources, lending, corporate sector, public and private partnership, war challenges.
Keywords: innovation and investment development; banking institutions; digitalization; financial innovations; banking sector; real sector of the economy; innovation activity; investment strategies; investment resources; lending; corporate sector; public and private partnership; war challenges